2021
DOI: 10.1177/21582440211030623
|View full text |Cite
|
Sign up to set email alerts
|

Blended Learning for Diverse Classrooms: Qualitative Experimental Study With In-Service Teachers

Abstract: The concept of blended learning, a combination of online and face-to-face learning, has become popular in educational settings. Using qualitative methods, this study investigates the role of blended learning and in-service teachers’ perceptions. Blended learning was used for 19 in-service teachers during their summer degree program at a Chinese university. After the course, teachers were asked to write their reflections on blended learning, its role in diverse classrooms, and using it in their teaching career.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 58 publications
0
39
0
Order By: Relevance
“…In contrast, others depended on external support, such as family support. This study also revealed that, at first, many of the teachers had a negative perception towards online learning, which affected teachers' and students' confidence and motivation [7,54,55]. However, they gradually recognized the benefits that online teaching and learning could offer.…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…In contrast, others depended on external support, such as family support. This study also revealed that, at first, many of the teachers had a negative perception towards online learning, which affected teachers' and students' confidence and motivation [7,54,55]. However, they gradually recognized the benefits that online teaching and learning could offer.…”
Section: Discussionmentioning
confidence: 72%
“…The disconnection between instructional approaches and learning needs influences the students' social and intellectual development to function in the modern world [39]. Hence, teachers need to shift to interactive teaching methods to help students advance their thinking ability and increase their interest in education [7,37]. Considering the traditional learning methods used in China, we argue that introducing online learning due to COVID-19 could be a 'blessing in disguise' for the country's higher education system.…”
Section: Teaching and Learning During The Covid-19mentioning
confidence: 98%
See 3 more Smart Citations